Menuju Keseimbangan Baru Antara Keselamatan Kondisi Ekonomi Dan Keselamatan Kondisi Kesehatan Di Tengah Pandemi (Covid 19) Kabupaten Kutai Kartanegara (Sebuah Perspektif Akademik) - Iskandar Iskandar (JEMI is managed and published by the Management Study Program, Faculty of Economics and Business, Kutai Kartanegara University. Institutional legality is reflected in the ISSN number: 1411-9560 published by LIPI in 2003 as a manifestation of the comm, 2022)
The management of the COVID-19 pandemic in this area is racing towards a balance between the safety of economic conditions and overall health conditions. This management is expected to prioritize saving lives as much as possible in the short term with the disaster relief paradigm, and then economic recovery and prosperity in the medium and long term. Social safety net during disaster relief is needed not only for the poor but also vulnerable middle-class people. A distribution policy mix is needed to accelerate the process and the quality of disbursements.Policies for Micro, Small and Medium Enterprises and banks are directed at reducing liquidity. In the mid-term recovery process, the focus of the policy is on reducing pressure from the supply side. Ensuring the business world can operate immediately, maintaining the sustainability of the logistics sector and encouraging industrial independence. Keywords : safety of economic conditions and overall health conditions.